PENGARUH MOTIVASI , KOMPENSASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. MITSUBISHI SRIKANDI DIAMOND MOTORS - Gunawan, Rio (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
This study aims to analyze the effect of Motivation, Compensation, and Competence Employee performance. The population in this study are employees at PT. Mitsubishi Heroine Diamond Motors. This study aims to describe the results of the phenomena that occur at PT. Mitsubishi Srikandi Diamond Motors. The sample used was 40 respondents. The sampling method uses the Quantitative Method. Method of collecting data using a survey method, the research instrument is a questionnaire. Data analysis method using Partial Least Square. This study proves that motivation has an effect significant positive effect on employee performance, Compensation has a significant positive effect on employee performance, and competence has a significant positive effect on employee performance at PT. Mitsubishi Srikandi Diamond Motors.